Identification of the Plasmid-Mediated Colistin Resistance Gene mcr-1 in Escherichia coli Isolates From Migratory Birds in Guangdong, China - Zhang, Yan; Kuang, Xu; Liu, Juan; Sun, Ruan-Yang; Li, Xing-Ping; Sun, Jian; Liao, Xiao-Ping; Liu, Ya-Hong; Yu, Yang (Frontiers in Microbiology, 2021)
We determined the prevalence and transmission characteristics of mcr-1 positive Escherichia coli (MCRPEC) isolates from migratory birds in Guangdong, China. We identified 22 MCRPEC from 303 migratory bird fecal samples (7.3%) in Guangzhou, Zhaoqing and Futian. The mcr-1 gene co-existed with 24 other types of antibiotic resistance genes (ARG) and 11 ARGs were highly prevalent at levels >50%. The MCRPEC displayed a diversity of sequence types (ST) and 19 distinct STs were identified with ST10 as the most prevalent. In addition, these MCRPEC from birds were closely related phylogenetically with those from other sources in China. Whole genome sequencing analysis demonstrated that mcr-1 was located on IncX4 (n=9, 40.9%), IncI2 (n=5, 22.7%) and IncP (n=1, 4.5%) plasmids and the latter shared an identical plasmid backbone with other sources. These findings highlight the significance of migratory birds in the transmission of antibiotic resistance and provide powerful evidence that migratory birds are potential transmitters of antibiotic resistance.